2020
DOI: 10.1002/ped4.12206
|View full text |Cite
|
Sign up to set email alerts
|

Short fixation with a 3‐rod technique for posterior hemivertebra resection in children younger than 5 years old

Abstract: Congenital hemivertebra is commonly treated with posterior hemivertebra resection with bilateral transpedicular fixation. However, implant-related complications are common in children younger than 5 years old who undergo this surgical procedure. objective: To present the preliminary clinical and radiological outcomes of children younger than 5 years old treated by posterior hemivertebra resection and 3-rod fixation technique. methods: From January 2016 to December 2017, 14 consecutive patients of congenital sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The frequency of complications ranged from 0 to 41% ( 27 , 28 , 32 , 33 , 35 42 ) and complications included wound infection, adding-on phenomenon, pseudoarticulation formation, postoperative progression of scoliosis, the offset of the internal fixation, and pedicle fractures. In our previous study ( 43 ), it showed that 14 patients with CS younger than 5 years of age accepted short fixation for posterior hemivertebra resection, which had a mean correction rate of 77.86% and no surgery-related complications. With a mean correction rate of 90.84%, posterior hemivertebra resection combined with segmental fusion was more effective in patients with TACS.…”
Section: Discussionmentioning
confidence: 92%
“…The frequency of complications ranged from 0 to 41% ( 27 , 28 , 32 , 33 , 35 42 ) and complications included wound infection, adding-on phenomenon, pseudoarticulation formation, postoperative progression of scoliosis, the offset of the internal fixation, and pedicle fractures. In our previous study ( 43 ), it showed that 14 patients with CS younger than 5 years of age accepted short fixation for posterior hemivertebra resection, which had a mean correction rate of 77.86% and no surgery-related complications. With a mean correction rate of 90.84%, posterior hemivertebra resection combined with segmental fusion was more effective in patients with TACS.…”
Section: Discussionmentioning
confidence: 92%
“…the convex epiphyseal block, and hemivertebrectomy (18). For congenital scoliosis secondary to hemivertebral deformity, posterior hemivertebrectomy is preferred (10,19,20). The age at which the patient should undergo surgery is controversial, but there is a greater consensus that surgery before 3 years of age yields better outcomes (1,14,19,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have demonstrated that the pedicle screw system is safe and effective in pediatric patients (12, 26), the is not well developed in very young children (11,25). Especially for children under 5 years old, it is difficult to maintain a good internal fixation position (20), and the failure of internal fixation implantation is a challenge for hemivertebrectomy in young children (27), mainly including complications such as pedicle fracture and internal fixation prolapse (10)(11)(12)(13). In 2003, Ruf et al (12) reported that among children under 6 years of age who underwent posterior hemivertebrectomy with transpedicular instrumentation, 3 out of 28 had failed internal fixation and 2 out of 28 had pedicle fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation